Perception Analysis Of PNJ Civil Engineering Students Toward Main Course Using Importance Performance Analysis Method: Analisis Persepsi Mahasiswa Teknik Sipil PNJ Terhadap Mata Kuliah Inti Dengan Metode Importance Performance Analysis - Amalia, Amalia; Hasan, Muhammad Fathur Rouf; Yanuarini, Erlina; Setiawan, Yanuar; Saputra, Jonathan (Universitas Muhammadiyah Sidoarjo, 2021)
The suitability between expectations and reality of the quality of education students get during college affects students' perceptions of education quality in a study program. Information on the achievement of the implementation of main courses subjects and the teaching and learning process can be used as a basis for evaluating and mapping the gaps between the curriculum and the teaching and learning process with the required competencies. This study aims to determine students' perceptions of core subjects' learning outcomes in the D3 KS and D3 KG Pograms, Department of Civil Engineering PNJ. The method used in this research is the survey method, with purposive random sampling and descriptive analysis approach. Meanwhile, the performance and gap analysis use the Importance-Performance Analysis (IPA) method. The results denote that the students' perceptions of the learning outcomes of the main courses of the D3 KG and D3 KS Programs, Department of Civil Engineering PNJ showed promising results. The IPA analysis shows that six of the seven D3 KG Study Program main courses are in Quadrant II, and six of the eight D3 KS Program main courses are also in Quadrant II.